2019
DOI: 10.1186/s12872-019-1184-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ezetimibe/simvastatin 10/10 mg versus Rosuvastatin 10 mg on carotid atherosclerotic plaque inflammation

Abstract: Background: Using 18 F-fluorodeoxyglucose ( 18 FDG) positron emission tomography-computed tomography (PET/CT) imaging, we examined the effects of ezetimibe/simvastatin 10/10 mg versus rosuvastatin 10 mg on carotid atherosclerotic plaque inflammation. Whether the combination therapy of ezetimibe with low-dose statin is as effective as potent statin monotherapy in attenuating carotid atherosclerotic plaque inflammation remains unclear.Methods: In this 2-by-2 factorial trial, 50 patients with 18 FDG uptake (targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Our findings suggest that statin therapy, either alone or in combination with ezetimibe, significantly reduced carotid temperatures in those patients. This is in line with recent studies, where both statin monotherapy and the combination of ezetimibe with either simvastatin or rosuvastatin reduced FDG carotid wall uptake in patients with recent acute coronary syndrome [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings suggest that statin therapy, either alone or in combination with ezetimibe, significantly reduced carotid temperatures in those patients. This is in line with recent studies, where both statin monotherapy and the combination of ezetimibe with either simvastatin or rosuvastatin reduced FDG carotid wall uptake in patients with recent acute coronary syndrome [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although robust data exist about the impact of statin therapy on carotid wall inflammation [ 16 , 17 , 18 ], few data exist regarding the impact of ezetimibe on top of statin therapy on arterial wall inflammatory activation. In specific, the combination of ezetimibe with statin, compared to statin monotherapy, exerts a similar anti-inflammatory effect on carotid atherosclerotic plaque [ 14 , 15 ]. It is noteworthy that in a recent study the combination of ezetimibe with low-dose rosuvastatin showed inferior carotid wall anti-inflammatory effect compared to high-dose rosuvastatin [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute coronary syndrome including ST-segment elevation myocardial infarction, non-ST-segment elevation myocardial infarction, and unstable angina was diagnosed based on the clinical symptoms, electrocardiography, and a rise in troponins. The trials used a common protocol with the only exception being the cholesterol-lowering medications; the effects of simvastatin/ezetimibe 10 mg/10 mg vs rosuvastatin 10 mg, [ 17 ] and rosuvastatin/ezetimibe 5 mg/10 mg vs rosuvastatin 20 mg on carotid atherosclerotic plaque inflammation were compared. [ 18 ] In each of these studies, patients were required to have carotid artery disease (diameter of stenosis, 20%–50%), acute coronary syndrome, and at least one carotid 18 FDG uptake lesion (target-to-background ratio (TBR) ≥ 1.6).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, PET/CT can detect even small changes in arterial wall inflammation, which is a unique property among other imaging techniques or biomarkers. So far, seven prospective studies have used scintigraphy to evaluate the impact of statins on carotid plaque inflammation by measuring target-to-background ratio (TBR) (n = 5 studies) [45][46][47][48] and/or standardized uptake value (SUV) (n = 3 studies) [39,49,50]. Most of them supported a significant reduction of arterial wall inflammation after either 3-month atorvastatin (10-80 mg/d) [46,[48][49][50] therapy, or 1-month atorvastatin (20 mg/d) [45] administration, or 6-month therapy with either simvastatin (10 mg/d), rosuvastatin (10 mg/d) [39], pitavastatin (2 mg/d), or pravastatin (10 mg/d) [39].…”
Section: Effects Of Statins On Fluorodeoxyglucose-positron Emission T...mentioning
confidence: 99%